Can Bitcoin be a stable investment? - Ismail Çelik (Financial Studies, 2020)
This study aims to analyze the volatility structure of Bitcoin returns, which became a popular investment after 2009. The Fractal Market Hypothesis (FMH) is chosen as the instrument to investigate the issue. By testing this hypothesis, the sudden price fluctuations in Bitcoin returns were tried to be determined. Daily closing price of Bitcoin between 04/2013-01/2019 were obtained from coinmarketcap. The fractal nature of Bitcoin market is tested with R/S, DFA, Periodogram and GPH models. The Hurst exponents show that FMH is valid in the Bitcoin market. Additionally, the effect of financial bubble formation and structural breaks on fractality is investigated through the ARFIMA-FIGARCH and ARFIMA-HYGARCH models. We observe that financial bubbles and regime changes increase the fractal structure (long memory) in the Bitcoin market.
Keywords: C58; G14; 330; Fractal Market Hypothesis; Hurst Exponent; Financial Bubbles; FIGARCH; HYGARCH